2022
DOI: 10.37398/jsr.2022.660312
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Hydrophobins in Medical Biotechnolog

Amol L. Salve,
Shreyash B. Apotikar,
Shreya V. Muddebihalkar
et al.

Abstract: Class I and class II Hydrophobins are small, low molecular weight cysteine-rich protein produced by filamentous fungi, of approximately 100 amino acids, whose size ranges between 5-20 kDa. Research over the last 10 years gave an improved insight into the applications of hydrophobins in the medical and pharmaceutical fields. The study of hydrophobins, self-assembly between hydrophobic and hydrophilic interfaces led to a better understanding of physical properties and their applications. Different coatings which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…While some proteins readily dissolve in aqueous buffers, others require denaturing agents, chaotropic reagents, or organic solvents to overcome insolubility barriers. Hydrophobins, unique proteins from filamentous fungi, offer versatile applications in fields such as food technology, pharmaceuticals, cosmetics, and materials science due to their amphiphilic nature and remarkable surface activity, but their hydrophobic nature complicates solubilisation and extraction process [37]. Krishnaswamy et al [38], showed that proteins extracted using TE (Tris + EDTA) and yeast-breaking buffer yielded concentrations exceeding 2 µg/mL, indicating insufficient extraction.…”
Section: Protein Solubilitymentioning
confidence: 99%
“…While some proteins readily dissolve in aqueous buffers, others require denaturing agents, chaotropic reagents, or organic solvents to overcome insolubility barriers. Hydrophobins, unique proteins from filamentous fungi, offer versatile applications in fields such as food technology, pharmaceuticals, cosmetics, and materials science due to their amphiphilic nature and remarkable surface activity, but their hydrophobic nature complicates solubilisation and extraction process [37]. Krishnaswamy et al [38], showed that proteins extracted using TE (Tris + EDTA) and yeast-breaking buffer yielded concentrations exceeding 2 µg/mL, indicating insufficient extraction.…”
Section: Protein Solubilitymentioning
confidence: 99%